2020
DOI: 10.1136/bmjgh-2020-002408
|View full text |Cite
|
Sign up to set email alerts
|

Which mechanisms explain the motivation of primary health workers? Insights from the realist evaluation of a maternal and child health programme in Nigeria

Abstract: IntroductionWell-trained, adequately skilled and motivated primary healthcare (PHC) workers are essential for attaining universal health coverage (UHC). While there is abundant literature on the drivers of workforce motivation, published knowledge on the mechanisms of motivation within different contexts is limited, particularly in resource-limited countries. This paper contributes to health workforce literature by reporting on how motivation works among PHC workers in a maternal and child health (MCH) program… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
20
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 17 publications
(22 citation statements)
references
References 46 publications
2
20
0
Order By: Relevance
“…This highlights that VHWs require a supportive environment to perform well. Our study supports other work that has highlighted the role of organisational capacity, culture and policies for health worker motivation, 28 and we have identified the importance of teamwork, task sharing and collegial support in this context. Our findings also support work that has found that CHWs are motivated when their peers and supervisors are supportive and encouraging, 20 and that skilled health facility managers and health workers create opportunities for CHWs to acquire new knowledge and skills.…”
Section: Discussionsupporting
confidence: 89%
See 3 more Smart Citations
“…This highlights that VHWs require a supportive environment to perform well. Our study supports other work that has highlighted the role of organisational capacity, culture and policies for health worker motivation, 28 and we have identified the importance of teamwork, task sharing and collegial support in this context. Our findings also support work that has found that CHWs are motivated when their peers and supervisors are supportive and encouraging, 20 and that skilled health facility managers and health workers create opportunities for CHWs to acquire new knowledge and skills.…”
Section: Discussionsupporting
confidence: 89%
“…This highlights that VHWs require a supportive environment to perform well. Our study supports other work that has highlighted the role of organizational capacity, culture and policies for health worker motivation, 28 and we have identified the importance of teamwork, task sharing and collegial support in this context.…”
Section: Figure 2 About Heresupporting
confidence: 90%
See 2 more Smart Citations
“…In a study similar to ours in Nigeria, 5 mechanisms were proposed to motivate ANC health care workers, (1) feeling supported, (2) feeling comfortable with work environment, (3) feeling valued, (4) morale and confidence to perform tasks and (5) companionship. [ 23 ]…”
Section: Discussionmentioning
confidence: 99%